PENGARUH PENDEKATAN JOYFUL LEARNING BERBANTUAN MEDIA SMART TV TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS V SDN 146 BENGO - Muhammad Idris Jafar; Muh. Ikhsan Sukaria; Esti Julviana Ningsih (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study uses a quantitative approach of pre-experimental type which aims to determine the differences in Mathematics learning outcomes of fifth grade students of SD Negeri 146 Bengo before and after the implementation of approach JL assisted by Smart TV media and to determine the effect of the implementation of approach JL assisted by Smart TV media on students' Mathematics learning outcomes. The research design is one group pretest-posttest design. The population of this study was all fifth grade students of SD Negeri 146 Bengo, Bone Regency, totaling 20 students using saturated sampling technique. The data collection technique used a multiple-choice test. The data analysis technique was descriptive and inferential statistical analysis. The results of the descriptive statistical analysis showed that the pretest score of students' Mathematics learning outcomes was in the very poor category with an average of 48.25, while the posttest score was in the good category with an average of 79.50. The results of the inferential statistical analysis using the paired samples t-test showed a t-value of 11.423 greater than the t-table of 2.093 with a significance level of 0.05. This indicates a significant influence on students' Mathematics learning outcomes before and after the implementation of the JL approach. The conclusion of the study is that the application of JL assisted by Smart TV media has a significant effect on the mathematics learning outcomes of fifth grade students of SD Negeri 146 Bengo.